MLearning scaffolding model for undergraduate English language learning: bridging formal and informal learning - Lim Abdullah, Muhammad Ridhuan Tony; Hussin, Zaharah; -, Asra; Zakaria, Abd Razak (Sakarya University, 2013)

(untitled)
Learning using mobile devices also known as mLearning is the current buzz word in the present debates over the use of technology in education. Although mLearning has a high prospect for future education, it is yet to be incorporated widely in mainstream formal education. The lack of a contemporary theory of learning and model for the mobile era has been one of the main issues hindering the incorporation. Although past studies have discussed learning theories and models for mLearning at great length, there is a wide gap in the investigation of theory and model for language-learning in the mobile context. Hence, this paper aims to describe how learners could be assisted in language-learning via supportive scaffolding using mobile devices at the undergraduate level using Gilly Salmon’s five-stage scaffolding model. This model is supported by Vygotsky’s Zone of Proximal Development as the basis of learning theory. A case study was conducted on undergraduate language learning in a private university in an attempt to seek how this model could be applied for mLearning. The results from the study revealed improvement in learners’ language performance but more importantly the results also suggested some adaptations to be made to the model in order to adapt it to language-learning in the mobile context. As mLearning should include informal learning, the key characteristic of the adapted model shows how formal learning and informal learning can be interwoven using mLearning.